Participation and Achievement in Mathematics: A Gender Perspective in Secondary School of Nepal - Sapkota, Hari Prasad (Research Journal, 2024)
This study sought to examine gender perspectives in participating in mathematics classes, interacting with teachers and peers, and the learning environment within schools for female students. The objectives of this study were to find the gender difference in the mathematics achievement of students and to identify the effect of gender in classroom participation of mathematics students at secondary school. A cross-sectional survey with 294 students from Ilam district was surveyed. Univariate and bivariate analysis were used to find the significant difference on achievement and chi-square test was used to find the association of participation of female students in different variables. There is significant difference between theachievement of boys and girls in mathematics at grade X (t = 2.508). The average achievement of boys was higher than that of girls. The effect of gender in different categorical variables viz; ethnicity, parental education, family income, attendance of students, interaction with teachers and peers had been done by bivariate analysis and the association was statistically significant. Educated family, better economic status of family, regular attendance in classroom, more interaction with teacher were the factors which is significantly associated with the participation of female students.